Budaya Keamanan, Keselamatan dan Kesehatan Lingkungan Sekolah (K3L): Kajian Sosiologis Komparatif Tentang Tata Kelola Sarana dan Prasarana Berbasis K3L pada Sekolah Menengah Pertama Islam Berbasis Pesantren dan Nonpesantren di Indonesia - Dewi Astuti; Muh. Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the management of school facilities and infrastructure (sarana dan prasarana/sarpras) based on Occupational Safety, Health, and Environment (Keamanan, Keselamatan, Kesehatan, dan Lingkungan Sekolah/K3L) through a comparative approach at SMP Islam Andalusia, a pesantren-based school, and SMP Muhammadiyah Kebasen, a non-pesantren school, both located in Kebasen District, Banyumas Regency. The study aims to describe and analyze four dimensions of the K3L management cycle planning, implementation, monitoring, and evaluation across both institutions. A descriptive qualitative comparative method was employed, with data collected through semi-structured in-depth interviews, systematic field observation, and document analysis. Data sources were selected using purposive sampling, involving school principals, vice principals for facilities, teachers, and students, as well as official school documents. Data analysis followed the thematic analysis model of Miles, Huberman, and Saldaña. The findings reveal that SMP Islam Andalusia implements a more structured, proactive, and well-documented K3L cycle compared to SMP Muhammadiyah Kebasen, which remains largely reactive and has yet to fully institutionalize its K3L management system. This difference is not primarily attributable to budget disparities, but rather to the internalization of Islamic values and the pesantren habitus, which organically cultivates a culture of discipline, order, and environmental cleanliness. The study concludes that the effectiveness of facility management based on K3L is fundamentally determined by the extent to which safety values have become an integral part of a school's institutional identity and culture. Accordingly, schools that have not yet adopted a systematic K3L cycle need to strengthen their planning, monitoring, and data-driven evaluation systems.